LITERATURE REVIEW ON THE EFFECT OF SOCIAL CUSTOMER RELATIONSHIP MANAGEMENT (SCRM) IN THE MALAYSIAN EVENT MANAGEMENT INDUSTRY - Rakesh, Sarpal; Cheah, Zi Yin (INTI International University, 2022)
This study aims to examine the impact of Social Customer Relationships Management in the Malaysia Event Industry and the result of Customer Engagement from social media experience. A total of 23 journal papers were thoroughly reviewed. This paper presents an insight into the importance of Customer Relationship Management in the Malaysian event industry and the transition of Traditional Customer Relationship Management to Social Customer Relationship management. Besides, it also focuses on implementing 5 Experiential Dimensions by Schmitt in social media activities to increase customer engagement. Finally, it discusses the level of customer engagement in social media activities and the outcomes.